Development of an Interactive Coding-Based Module on Food Chain Topics to Enhance Analytical and Logical Thinking Skills of Fifth-Grade Elementary Students - Wita Ermayanti; Fenny Roshayanti; Joko Sulianto (LPPM Universitas Pendidikan Mandalika, 2026)
This study aims to develop a valid, practical, and effective interactive coding-based module on the food chain topic in Natural Sciences (IPAS) to improve the analytical and logical thinking skills of fifth-grade elementary school students. The study employed a Research and Development (R&D) method using the 4D model (Define, Design, Develop, Disseminate). The trial subjects consisted of 21 fifth-grade students at SDN Kembangarum 2 Mranggen, Demak, Central Java. Data collection instruments included expert validation sheets, observation sheets, teacher and student response questionnaires, and pretest and posttest assessments. Data analysis was conducted using both qualitative and quantitative approaches, including N-gain analysis, normality and homogeneity tests, and paired-sample t-tests. The main findings show that: (1) the developed module integrates science concepts with coding using ScratchJr; (2) the module demonstrates a very high level of validity based on expert evaluations (average 95%) and practitioner assessments (average >94%); (3) the module is categorized as highly practical, with a practicality score of 91% based on teacher and student responses; and (4) the module is effective in improving students’ analytical and logical thinking skills, as indicated by an N-gain score of 0.7299 (high category) and a statistically significant difference between pretest and posttest results (p < 0.001). In addition, the findings indicate that the module contributes to transforming the science learning paradigm in elementary schools from conventional teacher-centered instruction to a more student-centered, interactive, creative, and technology-integrated learning process. Through coding activities, students are encouraged to actively explore concepts, solve problems systematically, and develop higher-order thinking skills, making science learning more meaningful and relevant to the demands of 21st-century education.